2017
DOI: 10.1007/s12282-017-0803-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of surveillance and prevention strategies in BRCA1/2 mutation carriers

Abstract: With quality adjustment, RRM, RRSO, and RRM&RRSO were all cost-effective preventive strategies in BRCA1/2 mutation carriers, with RRM&RRSO being the most cost-effective in BRCA1 and RRM in BRCA2. This result supports the inclusion of insurance coverage for BRCA mutation carriers in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…For BRCA1 PV carriers, two studies found that RRSO at the age of 35 was the most cost-saving [ 28 ] or cost-effective, with an ICUR of $2101/QALY [ 29 ], compared to other surgical prevention strategies (RRM or combined RRM and RRSO), chemoprevention (tamoxifen/oral contraceptives) and surveillance. Three other studies found that combined RRM and RRSO at the age of 40 [ 41 ], or combined RRM at the age of 35 with RRSO at the age of 45 [ 53 ] was the most cost-saving; RRM at the age of 30 with RRSO at the age of 35 was the most cost-effective, with an ICER of $835/LYG [ 47 ]. For BRCA2 PV carriers, two studies found that combined RRM and RRSO at the age of 35 was the most cost-effective, with an ICUR of $3125/QALY [ 28 ], ant that combined RRM and RRSO at the age of 40 was the most cost-saving [ 41 ], compared with other preventive strategies or surveillance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For BRCA1 PV carriers, two studies found that RRSO at the age of 35 was the most cost-saving [ 28 ] or cost-effective, with an ICUR of $2101/QALY [ 29 ], compared to other surgical prevention strategies (RRM or combined RRM and RRSO), chemoprevention (tamoxifen/oral contraceptives) and surveillance. Three other studies found that combined RRM and RRSO at the age of 40 [ 41 ], or combined RRM at the age of 35 with RRSO at the age of 45 [ 53 ] was the most cost-saving; RRM at the age of 30 with RRSO at the age of 35 was the most cost-effective, with an ICER of $835/LYG [ 47 ]. For BRCA2 PV carriers, two studies found that combined RRM and RRSO at the age of 35 was the most cost-effective, with an ICUR of $3125/QALY [ 28 ], ant that combined RRM and RRSO at the age of 40 was the most cost-saving [ 41 ], compared with other preventive strategies or surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…For BRCA2 PV carriers, two studies found that combined RRM and RRSO at the age of 35 was the most cost-effective, with an ICUR of $3125/QALY [ 28 ], ant that combined RRM and RRSO at the age of 40 was the most cost-saving [ 41 ], compared with other preventive strategies or surveillance. A study reported that RRSO at the age of 40 was the most cost-effective, with an ICUR of $5535/QALY [ 29 ], and another one found that RRM at the age of 35 was the most cost-saving [ 53 ]. A familial cancer service program incorporating multidisciplinary clinic/RRM/RRSO/breast screening for unaffected BRCA1/2 PV carriers was also found to be cost-effective compared to no intervention in one study using real world clinical data, with an ICUR of $23,353/QALY for BRCA1 and $34,831/QALY for BRCA2 [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gene-specific and age-specific probabilities of developing EC or OC were derived from published literature ( Table 2 ; eTable 1 in the Supplement ). 3 , 9 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Until age 75 years, EC risks range from 11.8% to 48.9% and OC risks from 3.0% to 17.4%. 3 We assumed that EC and OC diagnoses were independent events and that after 1 cancer diagnosis was made, a patient was no longer at risk of developing the other cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Actively conducting clinical research on HBOC in Japan is also crucial to understand the efficacy and safety of HBOC practice for patients in Japan. The cost-effectiveness of HBOC management should be given more consideration [ 19 ], and clinical trials are required to understand the clinical and genetic characteristics of BRCA variant carriers in Japan. Data from the national registry of BRCA genetic test-takers can be utilized in these studies.…”
Section: Discussionmentioning
confidence: 99%